Syntheses and biological activities of daunorubicin analogs with uncommon sugars - Zhu, L.; Cao, X.; Chen, W.; Zhang, G.; Sun, D.; Wang, P.G.
To study the e.ects of the sugar structure on the activity of anthracycline against cancer cells, six daunorubicin analogs containing di.erent uncommon sugars were synthesized. Their cytotoxicities were tested against colon cancer cells by MTS assay. The results showed that the aglycon without sugar moiety has 70-100-fold lower activity against cancer cells than daunorubicin derivatives with various uncommon sugars. It suggests that the sugar structure in daunorubicin plays a critical role in determining its anticancer activity. In the compounds with various sugars, the 40-OH of the sugar is an important determinant for their activity, while the axial-30-substituent in the sugar interferes with the binding of daunorubicins to DNA. Therefore, 2,6-dideoxy sugars are a better choice for generating biologically active daunorubicin analogs than 6-deoxysugars, 2,3,6-trideoxysugars, or 2,3,4,6- tetradeoxysugars.